2021
DOI: 10.3390/jpm11060577
|View full text |Cite
|
Sign up to set email alerts
|

A Portable Biodevice to Monitor Salivary Conductivity for the Rapid Assessment of Fluid Status

Abstract: The evaluation of fluid status can save adults from life-threatening conditions, but the current methods are invasive or time-consuming. Therefore, we developed a portable device for measuring salivary conductivity. This prospective observational study enrolled 20 volunteers with no history of systemic diseases. Participants were observed for 13 h, including water restriction for 12 h followed by rehydration with 1000 mL water within 1 h. Serum and urine biomarkers for fluid status, thirst scales, and salivary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…This is consistent with the national prevalence rate of 10.10% reported in a large-scale cohort study conducted in Taiwan in 2014, suggesting that our study participants can be considered representative of the general population [30]. Our previous study also showed a positive correlation between salivary conductivity and age or creatinine, and a negative correlation with eGFR [27,28]. These findings align with those of the current study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the national prevalence rate of 10.10% reported in a large-scale cohort study conducted in Taiwan in 2014, suggesting that our study participants can be considered representative of the general population [30]. Our previous study also showed a positive correlation between salivary conductivity and age or creatinine, and a negative correlation with eGFR [27,28]. These findings align with those of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…The portable device is easy-to-use and does not require specialized personnel to operate. Our initial data suggests a positive correlation between higher salivary conductivity and elevated fasting glucose levels, as well as an increased risk of developing chronic kidney disease [27][28][29]. However, further research is necessary to validate salivary conductivity as a reliable biomarker for diabetes.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Urine-specific gravity and urine osmolality are also very sensitive to changes in hydration status, but they lag behind body fluid turnover and are only moderately correlated with serum osmolality during acute dehydration 27 29 . Previous studies have shown that salivary conductivity is a rapid, real-time, and easy-to-administer screening tool for evaluating fluid status 15 , 16 . In addition, the saliva test method is simple and non-invasive, allowing for repeated measurements to monitor the fluid status during the period of hydration therapy in acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…To address these limitations, we developed a portable device for measuring salivary conductivity, which is highly associated with fluid status 15 , 16 . This allows for a non-invasive and real-time evaluation of fluid status, and the intensity of hydration treatment may be adjusted in real-time to improve clinical outcomes after acute stroke.…”
Section: Introductionmentioning
confidence: 99%